Quick Homework Help

# 7x+3=4x-6 ⚑ Flag

by angel0426 at August 28, 2011

You're going to have get both variables on the same side. So you start out: 7x+3=4x-6 7x+9=4x 9=4x-7x now you combine like terms (the x's are like terms) 9= -3x x=-3 Hope this helped!

Pandas August 28, 2011

7x+3=4x-6 7x+3-3=4x-6-3 7x=4x-9 7x+9=4x-9+9(ans 0 so that's why cancelled) 7x-7x+9=4x-7x 9=-3x 9/-3=-3/-3x -3=x study further on internet i pray u understand!

Anosha August 29, 2011

x=-3

Maestro September 22, 2011

yes

Chizzy September 27, 2011

x=3

alonte September 27, 2011

7x+3 = 4x-6 TWO RULES: (1st) Undo terms by using the opposite term (example: term +3 's opposite term is -3): 7x+3-3 = 4x-6 (2nd) What we do to one side we must do to the other sides: 7x+3-3 = 4x-6-3   As usual we combine like-terms:  7x+3-3 = 4x-6-3  7x(+3-3) = 4x(-6-3) 7x (cancel) = 4x(-9) We're left with: 7x = 4x-9   Again... TWO RULES: (1st) Undo terms by using the opposite term (example: term 4x 's opposite term is -4x):  7x = 4x-4x-9 (2nd) What we do to one side we must do to the other sides: 7x-4x = 4x-4x-9   As usual we combine like-terms: 7x-4x = 4x-4x-9 (7x-4x) = (4x-4x)-9 (3x) = (cancel)-9   We're left with: 3x = -9   Again... TWO RULES: (1st) Undo terms by using the opposite term (example: term 3x 's opposite term is /3 because 3x is 3*x): 3x/3 = -9 (2nd) What we do to one side we must do to the other sides: 3x/3 = -9/3 As usual we combine like-terms: 3x/3 = -9/3 3x/3 = -9/3 (3x/3) = (-9/3) (x) = (-3) We're left with: x = -3   You're answer is: x = -3

lucsant October 14, 2011

x =-3

akashkm99 October 17, 2011

Question :7x+3=4x-6 Soln: 7x + 3 = 4x -6           Take all the x term on one side and other on another side. While shifting a number from one side to another the sign of the number that is shifted  changes. = 7x -4x = -6-3 = 3x = -9  = x = -9 /3 = x= -3  Answer : x =  -3

Tedda_16 November 09, 2011

7x+3=4x-6 3x=-9 x=3

tameem December 27, 2011

7x+3=4x-6 putting x terms on one side,we get             7x-4x=-6-3                3x=-9                 dividing 9 by 3,we get                   x=-9/3 x=-3 best of luck.:-))

workhard February 21, 2012

-3

spankybones March 27, 2012

x=-3

umeshbagai1 June 27, 2012